Content of Workers’ Representation Under the Labour Code - Chochova, Maria (Yearbook of the Law Department, 2023)
The paper examines the rights and obligations of the representatives of workers and employees under Article 7, paragraph 2 and Article 7a of the Labour Code. The provisions establishing them have been analyzed in detail, the corresponding conclusions and proposals de lege ferenda have been made.